Analisis Peran Profil Pelajar Pancasila dalam membentuk karakter cinta tanah air siswa kelas 8 di sekolah SMPIT Al Ibrah Gresik - Permatasari, Vegi Ayu Indah; Rahmawati, Zuli Dwi (Fakultas Agama Islam, 2025)
Curriculum as a tool to achieve dynamic educational goals. Therefore, the curriculum needs to continue to be developed and refined so that it remains relevant to developments in science, technology and the needs of a developing society. Currently the curriculum used is the independent learning curriculum. The independent curriculum has a ptogram, namely the Pancasila Student Profile program. The aims of this research are (1) to determine the role of the Pancasila Student Profile in shaping students' character of love for their homeland, (2) to determine the impact of the role of the Pancasila Student Profile on the importance of loving their homeland. This type of research is qualitative descriptive research which describes the object or subject being studied absolutely without being influenced by personal opinions or views. The results of this research are the role of the Pancasila Student Profile as an indicator of student graduation, and the impact of the role of the Pancasila Student Profile, namely helping individuals become believers, devoted to God Almighty, global diversity, mutual cooperation, critical reasoning, independence and creativity.